Correlation between biometric and parasitologic data of mussels (Perna perna) from Ponta do Tinguí, Mangaratiba, RJ, Brazil - Cardozo, Tatiana Silveira Feijó; dos Santos, Ícaro Rodrigues; Berto, Bruno Pereira; Cardozo, Sergian Vianna; de Mesquita, Eliana de Fatima Marques; Lopes, Carlos Wilson Gomes (Brazilian Journal of Veterinary Medicine, 2012)
ABSTRACT. Cardozo T.S.F., Santos I.R., Berto B.P., Cardozo S.V., Mesquita E.F.M. & Lopes C.W.G. [Correlation between biometric and parasitologic data of mussels (Perna perna) from Ponta do Tinguí, Mangaratiba, RJ, Brazil.] Correlação entre dados biométricos e parasitológicos de mexilhões (Perna perna) da Ponta do Tinguí, Mangaratiba, RJ, Brasil. Revista Brasileira de Medicina Veterinária, 34(1):9-13, 2012. Programa de Pós-Graduação em Medicina Veterinária (HVPTPOA), Faculdade de Veterinária, Universidade Federal Fluminense, Rua Vital Brazil Filho, 64, Niterói, RJ 24230- 340, Brasil. E-mail: tatiana.cardozo@ymail.com The present study was to correlate the biometric and parasitological data obtained of shellfish collected from Ponta do Tinguí, Mangaraiba, RJ, Brazil. Initially, a total of 100 mussels was sent to laboratory for evaluation of biometric parameters by measuring the valves on their thickness, width and length, and also to verify the total weight or biomass. Then parasitological tests were performed through the techniques of concentration and staining to determine the presence of Cryptosporidium oocysts. In all samples of the biomass of mussels processed and submitted to parasitological assessment noted the presence of Cryptosporidium oocysts. When correlated by the Spearman correlation coefficient, biometric data and parasitological observed a negative correlation between the data analyzed, especially when confronted with the total weight of biomass and the average number of Cryptosporidium oocysts. Featuring an inversely proportional relationship between weight and total biomass found, and the number of oocysts present in this biomass. The negative correlation between parasitological and biometric data shows that the environmental contamination present in the study area is directly related to the growth rate of mussels as they filter-feeding animals, which is performed without any selective capacity.